Mechanical and Metallurgical Properties of Aluminium and Copper Sheets Joined by Cold Pressure Welding - Ozel, Kaan; Sahin, Mumin; Akdogan, Aysegul (ASSOC MECHANICAL ENGINEERS TECHNICIANS SLOVENIA, 2008)
Cold pressure welding is a special welding method that has been used in applications such as assembly of various parts at an increasing rate in recent years. In the present paper, cold pressure welding was applied to commercial purity aluminium and copper sheets as lap welding and a 150 metric ton hydraulic press was used for the process. As the surface roughness and the weld deformation ratia of aluminium sheets increased, tensile strength of the joints also increased Purchased specimens with original roughness had the lowest weld deformation as-is and it was not possible to join these sheets at 30% weld deformations. Fatigue tests showed that joined sheets resisted against low fluctuating tensile stresses. Hardness increases due to local hardening at the interface as a result of cold deformation. Also EDX (Energy Dispersive X-ray) measurements clearly show that Al-Cu joints contain an intermetallic compound layer at the interlace which does not affect the joint strength to a great extent. Results showed that the cold pressure welding technique in lap form resulted in strong Al-Al joints and the intermetallic layer formed in Al-Cu joints did not affect the joint strength to a great extent. (C) 2008 Journal of Mechanical Engineering. All rights reserved.
Keywords: cold pressure welding; metallography; mechanical properties; surface roughness; deformation ratio; OPTIMIZATION; PARAMETERS; STEEL; STATE; FOILS; Engineering